2003
DOI: 10.1200/jco.2003.05.128
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Single-Agent Versus Combination Chemotherapy in Indolent Follicular Lymphomas: A Study of the Cancer and Leukemia Group B

Abstract: There is no advantage to the initial use of the relatively intensive combination, CHOP-B, for patients with FSCL compared with the less toxic single agent, cyclophosphamide. However, in an unplanned subgroup analysis, patients with FML who received the combination experienced improved disease control and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 62 publications
1
43
0
1
Order By: Relevance
“…1,3,[19][20][21][22] They demonstrate that remissions can be achieved in a large proportion of patients but that an improvement in remission rate does not translate into a prolongation of TTF, RD, or even OS. 23,24 In contrast, recent data clearly demonstrate that the addition of rituximab to chemotherapy (R-chemo) has a significant impact on response rates and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[19][20][21][22] They demonstrate that remissions can be achieved in a large proportion of patients but that an improvement in remission rate does not translate into a prolongation of TTF, RD, or even OS. 23,24 In contrast, recent data clearly demonstrate that the addition of rituximab to chemotherapy (R-chemo) has a significant impact on response rates and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most studies show that about 20% of patients never relapse or die from the disease, for example, one study in the pre-rituximab era showed no recurrence of disease in a cohort of patients who were followed for 20 years. 5 These studies have illustrated that the biological behavior of follicular lymphoma is markedly heterogeneous.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The rational design of multidrug protocols ideally follows a number of guidelines. 7 Each drug in the prescribed protocol should exhibit substantial activity as a single agent for the cancer in question.…”
mentioning
confidence: 99%